Nickel-chromium-iron-aluminum alloy having excellent workability, creep strength and corrosion resistance and use thereof
By optimizing the chemical composition of nickel-chromium-ferro-aluminum alloys, a stable phase structure and protective oxide film are formed, the problem of insufficient alloy performance at high temperatures in the prior art is solved, and excellent high-temperature corrosion resistance, creep strength and processability are achieved.
Patent Information
- Application Number
- JP2022533611
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-12-03
- Filing Date
- 2020-12-04
- Publication Date
- 2025-04-28
- Estimated Expiration
- 2040-12-04
AI Technical Summary
The prior art is difficult to provide mass-produced nickel-based alloys with excellent high temperature corrosion resistance, good creep strength and good processability at high temperatures.
By optimizing the chemical composition of nickel-chromium-ferro-aluminum alloy, it ensures that its chromium and aluminum content ranges between 17-33% and 1.8-4.0%, and combining other elements such as silicon, manganese, titanium, tungsten, etc. to form a stable phase structure and protective oxide film, thereby improving its high-temperature performance and processability.
The alloy is achieved with excellent corrosion resistance and creep strength at high temperatures while maintaining good processability. It is suitable for absorbing pipes and heat exchange systems in high temperature applications such as solar tower power plants.
Smart Images

Figure 0007669364000009 
Figure 0007669364000010 
Figure 0007669364000011
Abstract
Description
[Technical field]
[0001] The present invention relates to a nickel-chromium-iron-aluminum wrought alloy which exhibits excellent high temperature corrosion resistance, good creep strength, and improved fabricability.
[0002] Austenitic nickel-chromium-iron-aluminium alloys with different nickel, chromium and aluminium contents have long been used in furnace construction and in the chemical and petrochemical industries, where good high-temperature corrosion resistance and good hot / creep strength are required.
[0003] Nickel alloys with different nickel, chromium and aluminum contents are also of great interest for use in solar tower power plants due to their properties. The installation consists of a field of mirror bodies (heliostats) arranged around a tall tower. The mirror bodies concentrate the sunlight on an absorber (solar receiver) attached to the top. The absorber consists of a tube system, which heats up a heat transfer medium. This medium circulates in a circulation section with an intermediate storage tank. By means of a heat exchanger system, the thermal energy is converted into electricity in a secondary circuit using a generator. The heat transfer medium is mainly a mixture of molten sodium and potassium nitrate salts, the maximum operating temperature of the salt is about 700°C, depending on the alloy used for the components (Kruizenga et al., Materials Corrosion of High Temperature Alloys Immersed in 600°C Binary Nitrate Salt, Sandia Report, SAND 2013-2526, 2013).
[0004] Above 700 °C, the melting and decomposition of potassium nitrate salts becomes noticeable, and the corrosion of the metal tubes progresses significantly. Therefore, the maximum use temperature is 600-700 °C, depending on the material. Materials used in the absorber are, in particular, Alloy 800H (material number 1.4876, UNS N08810) or Alloy 625 (material number 2.4856, UNS N06625) (see Table 1).
[0005] It should be noted that, in general, the hot corrosion resistance of the alloys shown in Table 1 improves with increasing chromium content. Al-containing alloys form a chromium oxide film (Cr2O3) under which there is a more or less closed aluminum oxide film (Al2O3). The addition of small amounts of elements with a strong oxygen affinity, for example yttrium or cerium, improves the oxidation resistance. The chromium content is slowly consumed during use in the area of use to form a protective film. Thus, the higher the content of the chromium element forming the protective film, the longer the life of the material will be, since it will be delayed until the chromium content falls below a critical value and oxides other than Cr2O3, such as oxides containing iron and / or nickel, form. The hot corrosion resistance can be further improved by adding aluminum and / or silicon. Above a certain minimum content, the consumption of chromium is reduced, since these elements form a closed film under the chromium oxide film.
[0006] In particular, a high carbon content improves hot strength or creep strength at a given temperature. However, high contents of solid solution strengthening elements such as chromium, aluminum, silicon, molybdenum and tungsten also improve hot strength. In the range of 500°C to 900°C, the addition of aluminum, titanium and / or niobium can improve strength by precipitating γ' and / or γ" phases.
[0007] Examples of prior art for these alloys are shown in Table 1. Alloys such as Alloy 602 CA (N06025), Alloy 693 (N06693), Alloy 603 (N06603), and Alloy 214 (N07208) are known to have superior corrosion resistance compared to Alloy 600 (N06600) and Alloy 601 (N06601) due to their high aluminum content of over 1.8%. Alloy 214, due to its high aluminum content, exhibits superior durability in a 60% sodium nitrate / 40% potassium nitrate salt melt (Kruizenga et al., Materials Corrosion of High Temperature Alloys Immersed in 600°C Binary Nitrate Salt, Sandia Report, SAND 2013-2526, 2013). On the other hand, alloys such as Alloy 602 CA (N06025), Alloy 693 (N06693), Alloy 603 (N06603) and Alloy 214 (N07208) have excellent hot strength or creep strength in the temperature range where molten nitrates are used due to their high carbon and aluminum content. Alloy 602 CA (N06025) and Alloy 603 (N06603) still have excellent hot strength or creep strength even at temperatures above 1000 °C. However, the workability is impaired by, for example, the high aluminum content, and the higher the aluminum content, the greater the impairment (for example, in the case of Alloy 693 (N06693) and Alloy 214 (N07208)). The same is true to a high extent for silicon, which forms a low-melting intermetallic phase with nickel. In particular, Alloy 602 CA (N06025) and Alloy 603 (N06603) have a high proportion of primary carbides, which limits their cold workability.
[0008] WO 2019 / 075177 discloses a solar tower system including an absorber tube, a storage tank, and a heat exchanger, all of which contain a molten salt at a temperature above 650° C. as a heat transfer medium, wherein the disclosure further discloses that at least one of the absorber tube, storage tank, and heat exchanger components is composed of (by weight) 25-45% Ni, 12-32% Cr, 0.1-2.0% Nb, up to 4% Ta, up to 5% Hg, and up to 5% Na. It is produced from an alloy containing 1% V, max 2% Mn, max 1.0% Al, max 5% Mo, max 5% W, max 0.2% Ti, max 2% Zr, max 5% Co, max 0.1% Y, max 0.1% La, max 0.1% Cs, max 0.1% other rare earths, max 0.20% C, max 3% Si, 0.05-0.50% N, max 0.02% B, and the balance Fe and impurities.
[0009] EP 0 508 058 A1 discloses an austenitic nickel-chromium-iron alloy consisting of (by weight) 0.12-0.3% C, 23-30% Cr, 8-11% Fe, 1.8-2.4% Al, 0.01-0.15% Y, 0.01-1.0% Ti, 0.01-1.0% Nb, 0.01-0.2% Zr, 0.001-0.015% Mg, 0.001-0.01% Ca, max 0.03% N, max 0.5% Si, max 0.25% Mn, max 0.02% P, max 0.01% S, the balance being Ni and unavoidable dissolution impurities.
[0010] U.S. Pat. No. 4,882,125 discloses a high chromium nickel alloy characterized by excellent resistance to sulfidation and oxidation at temperatures exceeding 1,093° C., excellent creep strength exceeding 200 at a stress of 2,000 PSI at temperatures exceeding 983° C., good tensile strength, and good ductility (both at room temperature and at high temperatures), the high chromium nickel alloy consisting of (by weight) 27-35% Cr, 2.5-5% Al, 2.5-6% Fe, 0.5-2.5% Nb, maximum 0.1% C, maximum 1% Ti and Zr each, maximum 0.05% Ce, maximum 0.05% Y, maximum 1% Si, maximum 1% Mn, and the balance Ni.
[0011] EP 0549286 A1 discloses a high temperature durable Ni-Cr alloy containing 55-65% Ni, 19-25% Cr, 1-4.5% Al, 0.045-0.3% Y, 0.15-1% Ti, 0.005-0.5% C, 0.1-1.5% Si, 0-1% Mn, and at least 0.005% of the sum of at least one of the elements of the group Mg, Ca, Ce, <0.5% of the sum of Mg+Ca, <1% Ce, 0.0001-0.1% B, 0-0.5% Zr, 0.0001-0.2% N, 0-10% Co, the balance being iron and impurities.
[0012] From DE 60004737 A1 a heat-resistant nickel-based alloy is known which contains ≦0.1% C, 0.01-2% Si, ≦2% Mn, ≦0.005% S, 10-25% Cr, 2.1-<4.5% Al, ≦0.055% N and at least one of the elements B, Zr and Hf in total 0.001-1%, whereby the aforementioned elements may be present in the following contents: B≦0.03%, Zr≦0.05%. 0.2%, Hf<0.8%, 0.01-15% Mo, 0.01-9% W, but the total content of Mo+W may be 2.5-15%, 0-3% Ti, 0-0.01% Mg, 0-0.01% Ca, 0-10% Fe, 0-1% Nb, 0-1% V, 0-0.1% Y, 0-0.1% La, 0-0.01% Ce, 0-0.1% Nd, 0-5% Cu, 0-5% Co, balance Ni. For Mo and W, the following formula must be satisfied: 2.5≦Mo+W≦15 (1)
[0013] DE 10 2015200881 A1 describes a tubular body made of austenitic steel for molten salts, in particular an absorption tube of a solar receiver with molten salt as heat transfer medium or another conduit for conveying molten salts, which has the following properties based on weight: 0-0.025% C, preferably 0.0095-0.024% C; 0.05-0.16% N; 2.4-2.6% Mo; 0.4-0.7% Si; 0.5-1.63% Mn; 0~0.0375% P; S from 0 to 0.0024%; 17.15-18.0% Cr; 12.0-12.74% Ni; 0.0025~0.0045% B; with the balance being Fe, and optionally normal impurities.
[0014] German Patent Application Publication No. 102012002514 describes a chromium alloy containing (by weight): 12-28% chromium, 1.8-3.0% aluminium, 1.0-15% iron, 0.01-0.5% silicon, 0.005-0.5% manganese, 0.01-0.20% yttrium, 0.02-0.60% titanium, 0.01-0.2% zirconium, 0.0002-0.05% magnesium, 0.0001-0.05% calcium, 0.03-0.11% carbon, 0.003-0.05% nitrogen, 0. A nickel-chromium-aluminum-iron alloy is described containing 0.005-0.008% boron, 0.0001-0.010% oxygen, 0.001-0.030% phosphorus, max. 0.010% sulfur, max. 0.5% molybdenum, max. 0.5% tungsten, balance nickel and normal process impurities, where the following relationship must hold: 7.7Cx*a<1.0, where a=PN if PN>0 and a=0 if PN≦0, where x=(1.0Ti+1.06Zr) / (0.251Ti+0.132Zr), PN=0.251Ti+0.132Zr-0.857N, where Ti, Zr, N, C are the concentrations of the elements in weight percent.
[0015] German Patent No. 102012013437 describes a chromium alloy containing (by weight): >25-28% chromium, >2-3.0% aluminum, 1.0-11% iron, 0.01-0.2% silicon, 0.005-0.5% manganese, 0.01-0.20% yttrium, 0.02-0.60% titanium, 0.01-0.2% zirconium, 0.0002-0.05% magnesium, 0.0001-0.05% calcium, 0.03-0.11% carbon, 0.02-0.11% carbide, 0.02-0.20 ... The use of a nickel-chromium-aluminium-iron alloy containing 0.003-0.05% nitrogen, 0.0005-0.008% boron, 0.0001-0.010% oxygen, 0.001-0.030% phosphorus, max 0.010% sulfur, max 0.5% molybdenum, max 0.5% tungsten, balance nickel and normal process impurities, in the manufacture of seamless tubes is described, where the alloy satisfies the following relationship: 0<7.7Cx*a<1.0 (2), if PN>0 then a=PN (3a), if PN≦0 then a=0 (3b), x=(1.0Ti+1.06Zr) / (0.251Ti+0.132Zr) (3c), and PN=0.251Ti+0.132Zr-0.857N (4) must hold, where Ti, Zr, N, and C are the concentrations of the elements in weight percent.
[0016] DE 1020120111161 A1 describes a nickel-chromium-aluminium alloy containing (in weight percent) 24-33% chromium, 1.8-4.0% aluminium, 0.10-7.0% iron, 0.001-0.50% silicon, 0.005-2.0% manganese, 0.00-0.60% titanium, 0.0002-0.05% each of magnesium and / or calcium, 0.005-0.12% carbon, 0.001-0.050% nitrogen, 0.0001-0.020% oxygen, 0.001-0.030% phosphorus, max. 0.010% sulphur, max. 2.0% molybdenum, max. 2.0% tungsten, the balance nickel and normal process impurities, where the following relationship is satisfied: Cr+Al>28 (2a), Fp≦39.9 (3a), Fp=Cr+0.272·Fe+2.36·Al+2.22·Si+2.48·Ti+0.374·Mo+0.538·W-11.8·C (4a) must hold, where Cr, Fe, Al, Si, Ti, Mo, W and C are the concentrations of the elements in weight percent.
[0017] US Patent No. 5,862,800 discloses a solar tower power plant for introducing solar energy into molten salt, using tubes of the same diameter and wall thickness made of alloy Alloy 625. The composition of Alloy 625 is given as follows: Cr 20-23%, Al≦0.4%, Fe≦5%, Si≦0.5%, Mn≦0.5%, Ti≦0.4%, C 0.03-0.1%, P≦0.02%, S≦0.015%, Mo 8-10%, Nb 3.15-4.15%, Ni balance (≧58%).
[0018] The present invention relates to a material having a sufficiently high chromium and aluminum content, Good phase stability · Good processability · Good corrosion resistance in air similar to Alloy 602 CA (N06025) · Good hot strength / creep strength The challenge was to design a nickel alloy that could be used for other purposes to demonstrate its
[0019] The object is to provide a nickel-chromium-iron-aluminium alloy containing (by weight) >17-33% chromium, 1.8-<4.0% aluminium, 0.10-15.0% iron, 0.001-0.50% silicon, 0.001-2.0% manganese, 0.00-0.60% titanium, 0.0002-0.05% each of magnesium and / or calcium, 0.005-0.12% carbon, 0.001-0.050% nitrogen, 0.0001-0.020% oxygen, 0.001-0.030% phosphorus, max 0.010% sulphur, max 2.0% molybdenum, max 2.0% tungsten, balance nickel and normal process impurities, with nickel ≧50%, for use in solar tower power plants using molten nitrates as the heat transfer medium, the alloy having the following relationship: Fp≦39.9 (2a) Fp=Cr+0.272*Fe+2.36*Al+2.22*Si+2.48*Ti+0.374*Mo+0.538*W-11.8*C (3a) must hold, where: Cr, Fe, Al, Si, Ti, Mo, W and C are the concentrations of the respective elements in weight percent; Cr, Fe, Al, Si, Ti, Nb, Cu, Mo, W and C are resolved by the alloy, which is the concentration in weight percent of the element.
[0020] Advantageous further embodiments of the subject matter of the invention can be taken from the associated dependent claims.
[0021] All alloy content data are in weight percent unless otherwise stated.
[0022] The distribution range of chromium element is >17~33%, and the preferred range can be set as follows: ->18~33% - 20~33% - 22~33% - 24~33% - 25~33% - 26~33% - 27~32% - 28~32% ->28~32% - 29~31%
[0023] The aluminum content is 1.8 - <4.0%, but again depending on the application of the alloy the preferred aluminum content can be set as follows: - 1.8~3.8% - 1.8~3.2% - 2.0~3.2% - 2.0~<3.0% - 2.0~2.8% - 2.2~2.8% - 2.2~2.6% - 2.5~<4.0% - >3.0~<4.0% - >3.2~<4.0% ->3.2~3.8% - >3.0~<3.5%
[0024] The iron content is in the range of 0.1-15.0%, and the preferred content can be set within the following distribution range according to the application scope: - 0.1~12.0% - 0.1~10.0% - 0.1~7.5% - 0.1~4.0% - 0.1~3.0% - 0.1~<2.5% - 0.1~2.0% - 0.1~<2.0% - 0.1~1.0% - 0.1~<1.0% - 1.0~15.0% - 1.25~15.0% ->2.5~15.0% ->4.0~15.0% ->4.0~12.0% ->7.0~15.0% ->7.0~10.5% - 7.5~10.5%
[0025] The silicon content is 0.001-0.50%. Preferably, Si can be set in the alloy within the following distribution range: - 0.001~<0.40% - 0.001~<0.25% - 0.001~0.20% - 0.001~<0.10% - 0.001~<0.05%
[0026] The same is true for elemental manganese, which may be present in the alloy at 0.001-2.0% or in the following range: - 0.001~0.50% - 0.001~<0.40% - 0.001~0.20% - 0.001~0.10% - 0.001~<0.05% - 0.005~<0.05%
[0027] The titanium content is 0.00-0.60%. Preferably, Ti is set in the alloy within the following distribution range: - 0.001~0.60% - 0.001~0.50% - 0.001~0.30% - 0.001~0.10% - 0.01~0.30% - 0.01~0.25% - 0.00~<0.02%
[0028] Magnesium and / or calcium may also be included with a content of 0.0002 to 0.05%. Preferably, these elements may be set in the alloy as follows: - 0.0002~0.03% - 0.0002~0.02% - 0.0005~0.02%
[0029] The alloy contains 0.005-0.12% carbon, which is preferably set in the alloy within the following distribution range: - 0.01~<0.12% - 0.005~0.10% - 0.005~<0.08% - 0.005~<0.05% - 0.01~0.03% - 0.01~<0.03% - 0.02~0.10% - 0.03~0.10%
[0030] The same applies to the nitrogen element, which is contained at a content of 0.001 to 0.05%. The preferred content can be shown as follows: - 0.003~0.04%
[0031] The alloy further comprises phosphorus in a content of 0.001 to 0.030%. The preferred contents can be indicated as follows: - 0.001~0.020%
[0032] The alloy further comprises oxygen with a content of 0.0001 to 0.020%, in particular 0.0001 to 0.010%.
[0033] Elemental sulfur is present in the alloy as follows: - Sulfur max 0.010%
[0034] Molybdenum and tungsten, either alone or in combination, are present in the alloy in a maximum content of 2.0% each. The preferred contents can be shown as follows: - Molybdenum 1.0% max - W max. 1.0% - Mo max <0.50% - W max<0.50% - Mo max <0.10% - W max<010% - Mo max <0.05% - W max<0.05%
[0035] In order to obtain sufficient phase stability, the following relationship is satisfied: Fp≦39.9 (2a) Fp=Cr+0.272*Fe+2.36*Al+2.22*Si+2.48*Ti+0.374*Mo+0.538*W-11.8*C (3a) must hold, where: Cr, Fe, Al, Si, Ti, Mo, W and C are the concentrations of the respective elements in weight percent.
[0036] The preferred ranges can be set as follows: Fp≦38.4 (2b) Fp≦36.6 (2c)
[0037] The nickel content is greater than or equal to 50%. The nickel content may preferably be set as follows: - ≥ 55% or > 55% - ≥ 60% or > 60% - ≥ 65% or > 65% - ≥ 68% or > 68%
[0038] Optionally, the yttrium element can be set to a content of 0.001-0.20% in the alloy. Preferably, Y can be set to a distribution range in the alloy as follows: - 0.001~0.15% - 0.001~0.10% - 0.001~0.08% - 0.001~<0.045% - 0.01~<0.045%
[0039] Optionally, the lanthanum element can be set to a content of 0.001-0.20% in the alloy. Preferably, La can be set to a distribution range in the alloy as follows: - 0.001~0.15% - 0.001~0.10% - 0.001~0.08% - 0.001~0.04% - 0.01~0.04%
[0040] Optionally, the cerium element can be set to a content of 0.001-0.20% in the alloy. Preferably, Ce can be set to a distribution range in the alloy as follows: - 0.001~0.15% - 0.001~0.10% - 0.001~0.08% - 0.001~0.04% - 0.01~0.04%
[0041] Optionally, when cerium and lanthanum are added simultaneously, cerium mischmetal (a mixture of about 50% Ce, about 25% La, about 15% Pr, about 5% Nd, Sm, Tb and Y) can be used in a content of 0.001-0.20%. Preferably, the cerium mischmetal can be set in the alloy within the following distribution range: - 0.001~0.15% - 0.001~0.10% - 0.001~0.08% - 0.001~0.04% - 0.01~0.04%
[0042] Optionally, the niobium element can be set in the alloy at a content of 0.00-1.10%. Preferably, the niobium element can be set in the alloy at a distribution range as follows: - 0.001~<1.10% - 0.001~<0.70% - 0.001~<0.50% - 0.001~0.30% - 0.001~<0.30% - 0.001~<0.20% - 0.01~0.30% - 0.10~1.10% - 0.20~0.70%
[0043] If niobium is present in the alloy, an additional term for niobium must be added to equation (3a) as follows: Fp=Cr+0.272*Fe+2.36*Al+2.22*Si+2.48*Ti+1.26*Nb+0.374*Mo+0.538*W-11.8*C (3b) where Cr, Fe, Al, Si, Ti, Nb, Mo, W and C are the concentrations of the respective elements in weight percent.
[0044] Optionally, zirconium The content is 0.001 to 0.20%. Preferably, zirconium can be set within the following range in the alloy: - 0.001~0.15% - 0.001~<0.10% - 0.001~0.07% - 0.001~0.04% - 0.01~0.15% - 0.01~<0.10%
[0045] Optionally, the hafnium content is 0.001-0.20%. Preferably, the hafnium is set in the alloy within the following distribution range: - 0.001~0.15% - 0.001~<0.10% - 0.001~0.07% - 0.001~0.04% - 0.01~0.15% - 0.01~<0.10%
[0046] Optionally, the alloy may contain 0.001 to 0.60% tantalum.
[0047] Preferably, Ta may be set in the alloy within the following distribution range: - 0.001~0.60% - 0.001~0.50% - 0.001~0.30% - 0.001~0.10% - 0.001~<0.02% - 0.01~0.30% - 0.01~0.25%
[0048] Optionally, elemental boron may be included in the alloy as follows: - 0.0001~0.008%
[0049] The preferred content can be expressed as follows: - 0.0005~0.008% - 0.0005~0.004%
[0050] Additionally, the alloy may optionally contain 0.0-5.0% Cobalt, which may be further limited as follows: - 0.001~5.0% - 0.01~5.0% - 0.01~<5.0% - 0.01~2.0% - 0.1~2.0% - 0.1~<2.0% - 0.001~0.5
[0051] Additionally, the alloy may contain up to 0.5% copper.
[0052] Copper content may be further limited as follows: - up to 0.20% - up to 0.10% - up to 0.05% - <0.05% - up to 0.015% - <0.015%
[0053] If the alloy contains copper, an additional term for copper must be added to equation (3a) as follows: Fp=Cr+0.272*Fe+2.36*Al+2.22*Si+2.48*Ti+0.477*Cu+0.374*Mo+0.538*W-11.8*C (3c) where Cr, Fe, Al, Si, Ti, Cu, Mo, W and C are the concentrations of the respective elements in weight percent.
[0054] If niobium and copper are present in the alloy, then equation (3a) must contain additional terms for niobium and copper, as follows: Fp=Cr+0.272*Fe+2.36*Al+2.22*Si+2.48*Ti+1.26*Nb+0.477*Cu+0.374*Mo+0.538*W-11.8*C (3d) where Cr, Fe, Al, Si, Ti, Nb, Cu, Mo, W and C are the concentrations of the respective elements in weight percent.
[0055] Additionally, the alloy may contain up to 0.5% vanadium.
[0056] The vanadium content may be further limited as follows: - up to 0.20% - up to 0.10% - up to 0.05%
[0057] Finally, the impurities may further include the elements lead, zinc and tin in the following contents: Pb max. 0.002% Zn max. 0.002% Sn max 0.002%
[0058] Furthermore, optionally, the following relationship, which indicates particularly good processability: Fa≦60 (4a) Fa = Cr + 20.4 * Ti + 201 * C (5a) can be satisfied, where: Cr, Ti and C are the concentrations of the elements in weight percent. Preferred ranges are as follows: Fa≦54 (4b) It can be set as follows.
[0059] If niobium is present in the alloy, an additional term for niobium must be added to equation (5a) as follows: Fa=Cr+6.15*Nb+20.4*Ti+201*C (5b) where Cr, Nb, Ti and C are the concentrations of the respective elements in weight percent.
[0060] Optionally, furthermore, the following relationship, which expresses particularly good hot strength or creep strength: Fk≧47 (6a) Fk=Cr+19*Ti+10.2*Al+12.5*Si+98*C (7a) can be satisfied, where: Cr, Ti, Al, Si and C are the concentrations of the respective elements in weight percent.
[0061] The preferred ranges are as follows: Fk≧49 (6b) Fk≧53 (6c) It can be set as follows.
[0062] If niobium and / or boron are present in the alloy, then equation (7a) must contain additional terms for niobium and / or boron, as follows: Fk=Cr+19*Ti+34.3*Nb+10.2*Al+12.5*Si+98*C+2245*B (7b) where Cr, Ti, Nb, Al, Si, C and B are the concentrations of the respective elements in weight percent.
[0063] The alloy according to the invention is preferably processed in a VOD (vacuum oxygen decarburization) or VLF (vacuum ladle furnace) plant after open melting. However, melting and casting in a vacuum (VIM) is also possible. After ingot casting or continuous casting, the alloy is annealed, if necessary, at temperatures between 900 ° C and 1270 ° C for 0.1 h to 100 h to the desired semi-finished product form, followed by an intermediate annealing, if necessary, at 900 ° C to 1270 ° C for 0.05 h to 100 h and hot forming. The surface of the material can be chemically and / or mechanically removed if necessary (and several times) and cleaned during and / or at the end. After the end of the hot forming, if necessary, an intermediate annealing can be carried out at 700 ° C to 1250 ° C under a protective gas, for example argon or hydrogen, for 0.1 min to 70 h, followed by cooling in air, in a stirred annealing atmosphere or in a water bath and cold forming to the desired semi-finished product form to a degree of forming of 98%. A solution treatment is then carried out at a temperature range of 700°C to 1250°C for 0.1 min to 70 h, optionally under a protective gas, e.g. argon or hydrogen, followed by cooling in air, in a stirred annealing atmosphere or in a water bath. If necessary, chemical and / or mechanical cleaning of the material surface can be carried out during and / or after the final annealing.
[0064] The alloy according to the present invention can be readily manufactured and used in the product forms of strip, sheet, rod, wire, longitudinal welded pipe, and seamless pipe.
[0065] These product forms are manufactured with an average particle size of 5 μm to 600 μm, with the preferred range being 20 μm to 200 μm.
[0066] The alloy according to the invention is preferably used in solar tower power plants that use molten nitrates as the heat transfer medium. The alloy according to the invention can be used in all components that come into contact with the molten salt.
[0067] The alloy according to the invention can in particular be used in the absorbers (solar receivers) of the towers of solar power plants and / or in the heat exchangers of the power generation circuits (for example via steam turbines) and / or in storage tanks and transport pipes.
[0068] The nitrate may preferably be a mixture of sodium and potassium nitrate salts.
[0069] This mixture may preferably be of the following composition: - 50-70% sodium nitrate and 50-30% potassium nitrate - 55-65% sodium nitrate and 45-35% potassium nitrate - 58-62% sodium nitrate and 42-38% potassium nitrate
[0070] Alternatively, a mixture of sodium nitrate, potassium nitrate and sodium nitride may be used.
[0071] If necessary, the salt mixture can also be used under a pure CO2 atmosphere.
[0072] The maximum use temperature is 800° C. The maximum use temperature may be limited as follows: - Maximum 750℃ - Maximum 700℃ - Maximum 680℃ - Maximum 650℃ - <650℃ - Maximum 620℃ - Maximum 600℃ - <600℃
[0073] Tests carried out phase stability At equilibrium Generated phase was calculated for different alloy variants with the JMatPro program from Thermotech. As a database for the calculations, the TTNI7 database for nickel-based alloys from Thermotech was used.
[0074] Formability is determined in a tensile test at room temperature according to DIN EN ISO 6892-1, where the yield strength R p0.2 , tensile strength R m , and breaking elongation A are measured. The original gauge length L0 of the broken test piece and the gauge length after breaking L U Calculate the elongation A from the elongation of A=(L U -L0) / L0100%=ΔL / L0100% The elongation at break is indexed according to the gauge length: For example, for A5, the gauge length L0 = 5·d0, where d0 = initial diameter of the circular specimen.
[0075] The tests were carried out on circular specimens with a gauge range diameter of 6 mm and a gauge length L0 of 30 mm. The specimens were taken transverse to the forming direction of the semi-finished product. The forming speed was R p0.2 = 10MPa / s, and R m = 6.7, 10 -3 The rate was 1 / s (40% / min).
[0076] The measured elongation A in a tensile test at room temperature can be used as an index of formability. A material with good processability has an elongation of at least 50%.
[0077] Hot Strength is measured by a hot tensile test according to DIN EN ISO 6892-2, where the yield strength R p0.2 , tensile strength R m , and the elongation at break A are determined analogously to the tensile test (DIN EN ISO 6892-1) at room temperature.
[0078] The tests were carried out on circular specimens with a gauge range diameter of 6 mm and an initial gauge length L0 of 30 mm. The specimens were taken transverse to the forming direction of the semi-finished product. The forming speed was R p0.2 = 8.33 = 10 -5 1 / s (0.5% / min), R m = 8.33 = 10 -41 / s (5% / min) (DIN EN ISO 6892-2).
[0079] The test specimen is placed in the tensile tester at room temperature and heated to the desired temperature without applying tensile force. After reaching the test temperature, it takes 1 hour (600°C) or 2 hours (700°C to 1100°C) to reach temperature equilibrium. Then, apply tensile force to the specimen so that the desired strain rate is maintained, and start the test.
[0080] The creep strength of a material increases with increasing hot strength, so hot strength is also used to evaluate the creep strength of various materials.
[0081] Corrosion resistance at high temperatures was examined in an oxidation test at 1000°C in air, during which the test was interrupted every 96 hours to measure the weight change of the test piece due to oxidation. During the test, the test piece was placed in a ceramic crucible, and the spalled oxide was collected, allowing the weight of the spalled oxide to be measured. The sum of the weight change of the test piece (net weight change) and the weight of the spalled oxide is the total weight change of the test piece. The specific weight change is the weight change per unit surface of the test piece. In the following, the specific net weight change is referred to as m Netto , the specific total weight change is m Brutto , the change in specific weight of the spalled oxide is m spall The tests were carried out on specimens approximately 5 mm thick. Three specimens were taken from each batch, with the values shown being the average of the three specimens.
[0082] Description of characteristics - Corrosion resistance in molten salt Kruizenga et al. (2013, Materials Corrosion of High Temperature Alloys Immersed in 600°C Binary Nitrate Salt) tested the corrosion resistance of nickel alloys Alloy 625 (N06625), Alloy 120 (N08120), Alloy 230 (N02230), Alloy 242 (N10242), and Alloy 214 (N07208) (Table 1) at 600°C in a molten salt consisting of 60% sodium nitrate and 40% potassium nitrate flowing with air. The analysis results of the alloys used are shown in Table 2. After the test, the oxide film was removed from the metal surface and the weight of the test specimen was measured before the test, after the test, and after the oxide film was removed to determine the weight of the oxide film. From this, the weight loss (amount of scale removed) of the test specimen surface before the test was calculated.
[0083] Table 3 shows the corrosion rate after 3000 hours, on the one hand, and the amount of scale removed (mg / cm 2 ) and the other is expressed as metal loss (μm / year). The alloy Alloy 214 shows the lowest corrosion rate of 5.7 μm / year at an aluminum content of 4.5%, followed by Alloy 224 at an aluminum content of 3.8% and a corrosion rate of 8.3 μm / year. All other nickel alloys tested (Alloy 625, Alloy 120, Alloy 242, and Alloy 230) show much higher corrosion rates of more than 16.8 μm / year at an aluminum content of less than 0.5%. Alloy 214 and Alloy 224 form an aluminum oxide film that provides good protection against molten nitrates. If the aluminum content is too low, as in the alloys Alloy 625, Alloy 120, Alloy 242, and Alloy 230, no aluminum oxide film is formed and the corrosion rate increases. Therefore, it is advantageous for the alloy used in the molten nitrates to have sufficient aluminum content to allow the formation of a closed aluminum oxide film.
[0084] In addition to excellent corrosion resistance in molten nitrates, the alloy according to the invention further possesses the following properties: - Good phase stability - Good processability - Good corrosion resistance in air similar to Alloy 602CA (N06025) - Good hot strength / creep strength - phase stability
[0085] In the nickel-chromium-iron-aluminium system with additions of Ti and / or Nb, various embrittled TCP (topologically close-packed) phases can form, depending on the alloying content, such as, for example, Laves, σ or μ phases, or embrittled η or ε phases (see, for example, Ralf Buergel, Handbuch der Hochtemperaturwerkstofftechnik, 3. Auflage, Vieweg Verlag, Wiesbaden, 2006, p. 70-374). The equilibrium phase fractions of N06690 of batch 111389, for example, as a function of temperature (see Table 4 for a typical composition) are calculated to be 720°C (T S BCC ) a significant proportion of α-chromium (BCC phase in Figure 1) is formed. The formation of this phase is very difficult because it is analytically very different from the base material. However, the solvus temperature T of this phase is known to be very low, as described for example for a variant of Alloy 693 (UNS 06693) in “E. Slevolden, JZ Albertsen. U. Fink, Tjeldbergodden Methanol Plant: Metal Dusting Investigations,” Corrosion / 2011, paper no. 11144 (Houston, TX: NACE 2011), p.15”. S BCCThis is quite possible if the temperature of formation of alloy 3 is very high. Figures 2 and 3 show the phase diagrams of the alloy 3 of Table 4 or the alloy 10 of the alloy 693 variant (from U.S. Pat. No. 4,882,125, Table 1). This phase is brittle and causes undesirable embrittlement of the material. The formation temperature T of alloy 3 S BCC is 1079°C, and the formation temperature T of Alloy 10 S BCC The calculated solvus temperature T is 939°C. "E. Slevolden, JZ Albertsen. U. Fink, Tjeldbergodden Methanol Plant: Metal Dusting Investigations," Corrosion / 2011, paper no. 11144 (Houston, TX: NACE 2011), p.15" does not include accurate analytical results for alloys in which α-chromium (BCC phase) occurs. However, among the examples shown for Alloy 693 in Table 4, the calculated solvus temperature T S BCC It is speculated that α-chromium may occur in the analytes with the highest solvus temperature (e.g., alloy 10). S BCC In the case of the alloys of the present invention, which have been developed by E. Slevolden, J. Z. Albertsen, and U. Fink, Tjeldbergodden Methanol Plant: Metal Dusting Investigations, Corrosion / 2011, paper no. 11144 (Houston, TX: NACE 2011), p.15, α-chromium was detected only near the surface. S BCC However, the lowest solvus temperature T S BCC It is desirable that the temperature be 939°C or lower, which corresponds to
[0086] This is especially true for the following formula: Fp≦39.9 (2a) Fp=Cr+0.272*Fe+2.36*Al+2.22*Si+2.48*Ti+1.26*Nb+0.477*Cu+0.374*Mo+0.538*W-11.8*C (3d) where: Cr, Al, Fe, Si, Ti, Nb, Cu, Mo, W and C are the concentrations of the elements in weight percent. From Table 4, which contains the prior art alloys, it can be seen that Fp is greater than 39.9 for alloy 8, alloy 3 and alloy 2, and is just 39.9 for alloy 10. T S BCC For all other alloys where Fp is less than 939°C, Fp≦39.9.
[0087] - Processability As an example of processability, formability will be considered here.
[0088] Alloys can be strengthened by several mechanisms, leading to high hot and creep strength. The addition of other elements can increase the strength more or less depending on the element (solid solution strengthening). Much more effective is the increase in strength due to small particles or precipitates (particle strengthening). This is achieved, for example, by the gamma prime phase in nickel alloys with the addition of Al or other elements, e.g. Ti, or by the addition of carbides in nickel alloys with chromium (see, for example, Ralf Buergel, Handbuch der Hochtemperaturwerkstofftechnik, 3. Auflage, Vieweg Verlag, Wiesbaden, 2006, p.358-369).
[0089] Increasing the content of γ' phase forming elements or the C content certainly improves the hot strength, but the formability is increasingly impaired even in the solution-treated state.
[0090] For materials with very good formability, the target elongation A5 in a tensile test at room temperature is 50% or more, and at least 45% or more.
[0091] This is especially true for the carbide-forming elements Cr, Nb, Ti and C, which have the following relationship: Fa≦60 (4a) Fa=Cr+6.15*Nb+20.4*Ti+201*C (5b) This is achieved when Cr, Nb, Ti and C are the concentrations of the elements in weight percent.
[0092] - Hot strength / creep strength At the same time, it is desirable for the yield strength or tensile strength at elevated temperatures to reach at least that of Alloy 601 (see Table 6). 600℃: proof stress R p0.2 >150MPa; Tensile strength R m >500MPa (8a,8b) 800℃: proof stress R p0.2 >130MPa; Tensile strength R m >135MPa (8c,8d)
[0093] The yield strength or tensile strength should be in the range of that of Alloy 602 CA (see Table 6). At least three of the following four relationships should hold: 600℃: proof stress R p0.2 >250MPa; Tensile strength R m >570MPa (9a,9b) 800℃: proof stress R p0.2 >180MPa; Tensile strength R m >190MPa (9c,9d)
[0094] Requirements 8a, 8b, 8c and 8d are, in particular, based on the following relationship for the main strengthening elements: Fk≧47 (6a) Fk=Cr+19*Ti+34.3*Nb+10.2*Al+12.5*Si+98*C+2245*B (7b) is satisfied if Cr, Ti, Nb, Al, Si, C and B are the concentrations of the respective elements in weight percent.
[0095] - Atmospheric corrosion resistance: The alloy according to the invention has good corrosion resistance in air, similar to that of Alloy 602 CA (N06025). [Brief description of the drawings]
[0096] [Figure 1] FIG. 5 shows the relationship between the amount fraction (wt%) of phases in thermodynamic equilibrium and temperature for Alloy 690 (N06690) of a typical batch example 111389 (Tables 5a and 5b). [Diagram 2] FIG. 1 is a diagram showing the relationship between the amount ratio (wt%) of the phase in a thermodynamic equilibrium state and temperature for Alloy 693 (N06693), an example of Alloy 3 in Table 4. [Diagram 3] FIG. 1 is a graph showing the relationship between the amount ratio (wt%) of the phase in thermodynamic equilibrium and temperature for Alloy 693 (N06693), an example of Alloy 10 in Table 4.
[0097] Working Example: - Manufacturing: Tables 5a and 5b show the analysis of the batches melted on a laboratory scale and, for comparison, of some prior art batches melted on an industrial scale: Alloy 602CA (N06025), Alloy 690 (N06690), Alloy 601 (N06601). The prior art batches are marked with a T and the batches according to the invention with an E. The batches melted on a laboratory scale are marked with an L and the batches melted on an industrial scale with a G.
[0098] Laboratory-scale vacuum melted ingots of the alloys of Tables 5a and 5b were annealed at 900°C-1270°C for 8 hours, hot rolled and further intermediate annealed at 900°C-1270°C for 0.1-1 hour to a final thickness of 13 mm and 6 mm, respectively. The sheets thus produced were solution treated at 900°C-1270°C for 1 hour. The test pieces required for the measurements were prepared from these sheets.
[0099] For alloys melted on an industrial scale, samples were taken from in-house manufactured industrial sheets of appropriate thickness. From these sheets, the test specimens required for the measurements were prepared.
[0100] All alloy variations typically had grain sizes between 70 and 505 μm.
[0101] The following properties are compared for the batch examples in Tables 5a and 5b: - Corrosion resistance in molten nitrates - phase stability - Formability by tensile testing at room temperature - Hot strength / creep strength by hot tensile test - Corrosion resistance in air by oxidation test
[0102] - Corrosion resistance in molten nitrates: For batches 2301, 250129-250138, and 250147-250149, as well as batches 250164, 250311, and 250526, which were melted on a laboratory scale, the aluminum content is greater than or equal to 1.8%. This aluminum content is high enough that a closed aluminum oxide film can form under the chromium oxide film. They therefore meet the requirements for corrosion resistance in molten salts.
[0103] - Phase stability: Phase diagrams were calculated for selected prior art alloys in Table 4 and all experimental batches (Tables 5a and 5b), and the solvus temperatures T S BCC For the compositions in Table 4 or Tables 5a and 5b, the value of Fp was calculated using Equation 3d. Fp is the solvus temperature T S BCC The higher the solvus temperature T S BCCAll of the examples of N06693 with higher Fp than Alloy 10 have Fp>39.9. Therefore, the requirement of Fp≦39.9 (Equation 2a) is a good criterion for obtaining sufficient phase stability in the alloy. All of the experimental batches in Tables 5a and 5b meet the criterion of Fp≦39.9.
[0104] - Formability (processability): Table 6 shows the yield strength R at room temperature (RT) and 600°C. p0.2 , tensile strength R m and elongation A5, as well as tensile strength R at 800°C m is entered. Also, the values of Fa and Fk are entered.
[0105] In Table 6, the prior art alloy Alloy 602 CA batch examples 156817 and 160483 have relatively low room temperature elongations A5 of 36% and 42%, respectively, which are below the requirements for good formability. Fa is above 60, and therefore outside the range characterizing good formability. All alloys (E) according to the invention have elongations above 50%, thus meeting the requirements. All alloys according to the invention have Fa below 60, thus falling within the range for good formability. The elongations are high, especially when Fa is relatively low.
[0106] - Hot strength / creep strength: Prior art alloy Alloy 601 example batch 156656 in Table 6 is an example of minimum yield strength and tensile strength at 600°C or 800°C, while prior art alloy Alloy 602 CA examples batches 156817 and 160483 are examples of very good values of yield strength and tensile strength at 600°C or 800°C. Alloy 601 is representative of a material that meets the minimum hot strength or creep strength requirements described by relations 8a-8d. Alloy 602 CA is representative of a material that exhibits excellent hot strength or creep strength as described by relations 9a-9d. Both alloys have Fk values well above 47, with Alloy 602 CA also significantly exceeding the values for Alloy 601, indicating increased strength values for Alloy 602 CA. All alloys (E) according to the invention have proof stress and tensile strengths at 600°C or 800°C that are within or significantly exceed those of Alloy 601, and therefore satisfy the relations 8a-8d. They are within the range of values of Alloy 602 CA, and, except for batch 250526 and batch 250311, also satisfy the desirable requirements, i.e. three of the four relations 9a-9d. Fk is also greater than 47 or greater than 54 for all alloys according to the invention in the examples of Table 6, and therefore within the ranges characterized by good hot or creep strength. Among the experimental batches not according to the invention, batches 2297 and 2300 are examples where relations 8a-8d do not hold and Fk is also less than 47.
[0107] - Atmospheric corrosion resistance: Table 7 shows the specific weight change after 11 cycles of 96 hours at 1100°C in air, i.e., a total of 1056 hours. Table 7 shows the specific gross weight change, specific net weight change, and specific weight change of the spalled oxide after 1056 hours. The prior art alloy batch examples Alloy 601 and Alloy 690 show significantly higher total weight changes than Alloy 602 CA, with the total weight change of Alloy 601 being even more significantly higher than that of Alloy 690. Both form chromium oxide films that grow faster than aluminum oxide films. Alloy 601 still contains about 1.3% Al. This content is too low to form even a partially closed aluminum oxide film, so aluminum is oxidized inside the metal material under the oxide film (internal oxidation). This results in an increase in weight compared to Alloy 690. Alloy 602CA contains about 2.3% aluminum. Therefore, in this alloy, a closed aluminum oxide film can be formed under the chromium oxide film. This significantly suppresses the growth of the oxide film and the specific weight increase. All of the alloys (E) according to the present invention contain at least 2% aluminum, and therefore show a low or lower total weight gain similar to Alloy 602 CA. Also, like the batch example of Alloy 602 CA, all of the alloys according to the present invention show spalling within the measurement accuracy, but Alloy 601 and Alloy 690 show significant spalling.
[0108] Thus, the claimed limits of alloy "E" according to the present invention can be justified in detail as follows: If the chromium content is too low, the chromium concentration falls below the critical limit too quickly when the alloy is used in corrosive atmospheres, and a closed chromium oxide film cannot be formed. Therefore, a chromium content of more than 17% is the lower limit. If the chromium content is too high, the phase stability of the alloy decreases, especially at high aluminum contents above 1.8%. Therefore, a chromium content of 33% is the upper limit.
[0109] The aluminum oxide film forms under the chromium oxide film, slowing down the oxidation rate. If the aluminum content is less than 1.8%, the aluminum oxide film is incomplete and cannot fully exert its effect. If the aluminum content is too high, the workability of the alloy is impaired. Therefore, the aluminum content is limited to less than 4.0%.
[0110] A lower iron content increases the cost of the alloy. Below 0.1%, special starting materials must be used, which increases the cost disproportionately. Therefore, an iron content of 0.1% is set as the lower limit due to cost considerations. An increased iron content reduces the phase stability (formation of brittle phases), especially at high chromium and aluminum contents. Therefore, 15% iron is a reasonable upper limit to ensure the phase stability of the alloy according to the invention.
[0111] Silicon is necessary for the production of the alloy. Therefore, a minimum content of 0.001% is required. Workability and phase stability are impaired, especially with higher aluminum and chromium contents. Therefore, the silicon content is limited to 0.50%.
[0112] A minimum manganese content of 0.001% is required to improve workability. Manganese element reduces oxidation resistance and is therefore limited to 2.0%.
[0113] Titanium increases high temperature strength. Above 0.60%, oxidation behavior can deteriorate, so the maximum value is 0.60%.
[0114] Even very low magnesium and / or calcium contents improve workability due to the solidification of sulfur, thereby avoiding the formation of low-melting nickel-sulfur eutectic. Therefore, a minimum content of 0.0002% magnesium and / or calcium is required. Too high a content leads to the formation of intermetallic nickel-magnesium or nickel-calcium phases, which also significantly reduce workability. Therefore, the magnesium and / or calcium contents are limited to a maximum of 0.05%.
[0115] A minimum carbon content of 0.005% is necessary to obtain good creep strength. Carbon is limited to a maximum of 0.12%, because above this content this element reduces workability due to the excessive formation of primary carbides.
[0116] A minimum nitrogen content of 0.001% is required, which improves the workability of the material. Nitrogen is limited to a maximum of 0.05%, as the formation of coarse carbonitrides reduces workability.
[0117] The oxygen content must be 0.020% or less in order to manufacture the alloy. If the oxygen content is too low, the cost will be high. Therefore, the oxygen content must be 0.0001% or more.
[0118] Phosphorus is an interfacial active element and impairs oxidation resistance, so the phosphorus content is preferably 0.030% or less. If the phosphorus content is too low, the cost will increase. Therefore, the phosphorus content is 0.001% or more.
[0119] Since sulfur is an active surface element and impairs oxidation resistance, it is desirable to set the content as low as possible. Therefore, the maximum sulfur content is set at 0.010%.
[0120] The element molybdenum is limited to a maximum of 2.0% since it reduces the oxidation resistance.
[0121] Tungsten element also reduces oxidation resistance and is therefore limited to a maximum of 2.0%.
[0122] Nickel is the balance element. Too little nickel reduces the phase stability, especially with a high chromium content. Therefore, nickel must be at least 50%.
[0123] In order to obtain sufficient phase stability, the following relationship is satisfied: Fp≦39.9 (2a) Fp=Cr+0.272*Fe+2.36*Al+2.22*Si+2.48*Ti+0.374*Mo+0.538*W-11.8*C (3a) must hold, where: Cr, Fe, Al, Si, Ti, Mo, W and C are the concentrations of the elements in weight percent. The limitations on Fp and the possible inclusion of other elements have been justified in detail above.
[0124] If necessary, the oxidation resistance can be further improved by adding oxygen-compatible elements such as yttrium, lanthanum, cerium, and cerium mischmetal, which are incorporated into the oxide film and block oxygen diffusion paths at the grain boundaries.
[0125] A minimum yttrium content of 0.001% is required to obtain the oxidation resistance enhancing effect of yttrium, and the upper limit is set at 0.20% due to cost considerations.
[0126] A minimum lanthanum content of 0.001% is required to obtain the oxidation resistance enhancing effect of lanthanum, and the upper limit is set at 0.20% due to cost considerations.
[0127] To obtain the oxidation resistance enhancing effect of cerium, a minimum cerium content of 0.001% is required, and for cost reasons the upper limit is set at 0.20%.
[0128] To obtain the oxidation resistance improvement effect of cerium mischmetal, a minimum content of 0.001% cerium mischmetal is required, and due to cost considerations, the upper limit is set at 0.20%.
[0129] Niobium can also be added to improve high temperature strength, if necessary. Increasing the content would result in a very high cost, so the upper limit is set at 1.10%.
[0130] If desired, the alloy may also contain tantalum, as it also improves high temperature strength and oxidation resistance. Higher contents are very cost-intensive, so the upper limit is set at 0.60%. A minimum content of 0.001% is required to be effective.
[0131] If necessary, the alloy zirconium It may also include. zirconium In order to obtain the effect of improving high-temperature strength and oxidation resistance, 0.001% zirconium A minimum content is required. Due to cost considerations, the upper limit is zirconium It is set at 0.20%.
[0132] Optionally, the alloy may also contain hafnium. A minimum hafnium content of 0.001% is required to obtain the high temperature strength and oxidation resistance benefits of hafnium. Cost considerations set an upper limit of 0.20% hafnium.
[0133] Boron can be added to the alloy if necessary, since it improves creep strength. Therefore, a content of at least 0.0001% is recommended. At the same time, this surface active element reduces oxidation resistance. Therefore, a maximum of 0.008% boron is prescribed.
[0134] The alloy may contain a maximum of 5.0% cobalt. Higher contents significantly reduce oxidation resistance.
[0135] Copper element is limited to a maximum of 0.5% since it reduces oxidation resistance.
[0136] The element vanadium is limited to a maximum of 0.5% since it reduces the oxidation resistance.
[0137] The element lead reduces oxidation resistance and is therefore limited to a maximum of 0.002%, as are zinc and tin.
[0138] Optionally, furthermore, the following relationship, which indicates particularly good workability for the carbide-forming elements chromium, titanium and carbon, is satisfied: Fa≦60 (4a) Fa = Cr + 20.4 * Ti + 201 * C (5a) can be satisfied, where: Cr, Ti and C are the concentrations of the respective elements in wt %. The limitations on Fp and the possible inclusion of other elements have been justified in detail above.
[0139] Optionally, the strength-increasing elements may further satisfy the following relationship, which represents particularly good hot strength or creep strength: Fk≧47 (6a) Fk=Cr+19*Ti+10.2*Al+12.5*Si+98*C (7a) can be satisfied, where: Cr, Ti, Al, Si and C are the concentrations of the elements in weight percent. The limitations on Fp and the possible inclusion of other elements have been justified in detail above.
[0140] [Table 1]
[0141] [Table 2]
[0142] [Table 3]
[0143]
Table 4
[0144]
Table 5
[0145]
Table 6
[0146]
Table 7
[0147]
Table 8
Claims
1. A composite material having (by weight): greater than 28-33% chromium, 1.8-to-less than 4.0% aluminum, 0.10-15.0% iron, 0.001-0.50% silicon, 0.001-2.0% manganese, 0.00-to-less than 0.02% titanium, 0.0002-0.05% each magnesium and / or calcium, 0.005-to-less than 0.03% carbon, 0.001-0.050% nitrogen, 0.000 1. A nickel-chromium-iron-aluminum alloy consisting of 1-0.020% oxygen, 0.001-0.030% phosphorus, max 0.010% sulfur, max 2.0% molybdenum, max 2.0% tungsten, balance nickel and normal process impurities, and greater than 50% nickel, wherein the nitrate is a mixture of sodium and potassium nitrate salts in a composition of 50-70% sodium nitrate and 50-30% potassium nitrate, and has the following relationship: Fp≦39.9 (2a) Fp=Cr+0.272*Fe+2.36*Al+2.22*Si+2.48*Ti+0.374*Mo+0.538*W-11.8*C (3a) must hold, where: Cr, Fe, Al, Si, Ti, Mo, W and C are the concentrations in weight percent of the elements, said alloy being used in all components that come into contact with said molten nitrates, and said alloy being usable up to a maximum temperature of 800°C.
2. 2. The alloy of claim 1, wherein the aluminum content is 1.8-3.8%.
3. 3. The alloy of claim 1 or 2, wherein the iron content is 0.1 to 12.0%.
4. The alloy of any one of claims 1 to 3, wherein the silicon content is from 0.001 to less than 0.40%.
5. The alloy of any one of claims 1 to 4, wherein the manganese content is from 0.001 to 0.50%.
6. An alloy according to any one of claims 1 to 5, further comprising an yttrium content of 0.001 to 0.20%.
7. An alloy according to any one of claims 1 to 6, further comprising a lanthanum content of 0.001 to 0.20%.
8. An alloy according to any one of claims 1 to 7, further comprising a cerium content of 0.001 to 0.20%.
9. An alloy as claimed in any one of claims 1 to 8, further comprising a cerium mischmetal content of 0.001 to 0.20%.
10. Furthermore, the niobium content is 0.0 to 1.1%, and a term of Nb is added to the formula (3a) to obtain: Fp=Cr+0.272*Fe+2.36*Al+2.22*Si+2.48*Ti+1.26*Nb+0.374*Mo+0.538*W-11.8*C (3b) 10. The alloy of any one of claims 1 to 9, wherein Cr, Fe, Al, Si, Ti, Nb, Mo, W and C are the concentrations in weight percent of the elements.
11. The alloy of any one of claims 1 to 10, further comprising a zirconium content of 0.001 to 0.20%.
12. The alloy of any one of claims 1 to 11, further comprising a hafnium content of 0.001 to 0.20%.
13. An alloy as claimed in any one of claims 1 to 12, further comprising a boron content of 0.0001 to 0.008%.
14. The alloy of any one of claims 1 to 13, further comprising 0.0 to 5.0% cobalt.
15. Further, it contains up to 0.5% copper, and a term for Cu is added to the formula (3a) to give: Fp=Cr+0.272*Fe+2.36*Al+2.22*Si+2.48*Ti+0.477*Cu+0.374*Mo+0.538*W-11.8*C (3c) 2. The alloy of claim 1, wherein Cr, Fe, Al, Si, Ti, Cu, Mo, W, and C are the concentrations in weight percent of the elements.
16. 16. The alloy of any one of claims 1 to 15, further comprising up to 0.5% vanadium.
17. 17. The alloy according to any one of claims 1 to 16, wherein the impurities are set to a content of max. 0.002% lead, max. 0.002% zinc, max. 0.002% tin.
18. 11. The alloy of claim 10, wherein for Nb-free alloys the following formulas hold: Fa≦60 (4a), Fa=Cr+20.4*Ti+201*C (5a), where Cr, Ti and C are the concentrations in weight percent of the elements, thereby achieving particularly good workability, or for Nb-containing alloys Fa=Cr+6.15*Nb+20.4*Ti+201*C (5b), where Cr, Nb, Ti and C are the concentrations in weight percent of the elements.
19. 2. The alloy according to claim 1, wherein for the alloy without B and Nb, the following formulas hold: Fk≧47 (6a), Fk=Cr+19*Ti+10.2*Al+12.5*Si+98*C (7a), where Cr, Ti, Al, Si and C are the concentrations in weight percent of the elements, thereby achieving particularly good hot strength / creep strength.
20. An alloy according to claim 10 or 13, in which for an alloy containing B and / or Nb the following equations hold: Fk≧47 (6a), Fk=Cr+19*Ti+34.3*Nb+10.2*Al+12.5*Si+98*C+2245*B (7b), where Cr, Ti, Nb, Al, Si, C and B are the concentrations in mass% of the elements in question, thereby achieving particularly good hot strength / creep strength.
21. 21. Use of the alloy according to any one of claims 1 to 20 as strip, sheet, wire, rod, longitudinal welded tube and seamless tube.
22. 21. Use of the alloy according to any one of claims 1 to 20 for the production of strip, sheet, wire, rod, longitudinal welded tubes and seamless tubes.
Citation Information
Patent Citations
Process for the production of a wrought nickel-iron-chromium-aluminum alloy with increased elongation in the tensile test
DE102015008322A1
Sulfiding corrosion resistance / oxidation-resistant alloy
JP1989312051A
High-temperature resisting and corrosion resisting ni-cr alloy
JP1994264169A
Austenite / nickel / chromium / iron alloy
JP1995216483A
Nickel-based heat-resistant alloy having excellent hot workability, weldability, and carburizing resistance
JP2001040443A